Community health profile focusing on disability in El Tronconal, Veracruz, Mexico - Lozano Tinoco, Itzel; Hernández Gámiz, Karla Ivanna; Gabriel Peralta, Tania Citlalli; Narave Moreno, Mirei Gabriela; Aguilar Acolt, Anel; Mota Morales, María de Lourdes (Horizonte Sanitario, 2025)
Objective. To estimate the prevalence of People with Disabilities (PWD) and understand the sociodemographic conditions of these individuals and their families in the rural locality of El Tronconal, municipality of Xalapa, Veracruz (Mexico). Materials and Methods. Descriptive, observational, and cross-sectional study with a quantitative approach. A convenience and systematized sampling method was used with a sample of 234 inhabitants. A household survey was applied, integrating sociodemographic and health aspects as well as indicators from the Model Disability Survey. The analysis was conducted using descriptive statistics. Results. The prevalence of disability in the community (10.68%) exceeds the national average (6.87%). One in ten people has some type of disability. Women experience higher rates of disability (64%), with neurological disabilities being the most common (28%). Children and adolescents are significantly represented (40%). The most frequent disabilities: visual (24%), motor (24%), auditory (20%), and communicative (4%). Main causes of disability: advanced age (40%), degenerative diseases (24%), birth conditions (20%), and accidents (4%). The three main functional limitations: difficulty seeing well (34.6%), moving well (10.2%), and hearing well (7.2%). About 7.6% of the population is at risk due to heart diseases, and 5.5% due to metabolic conditions. 40% of PWD and their families live in “very difficult” conditions. 47.6% of the population has low educational attainment, and 59.4% lack social security. Care is primarily provided by women without professional training or financial compensation (86.6%). 46.6% of PWD perceive a medium level of social respect, and 13.3% perceive a low level. Conclusions. The generation of primary data is crucial for recognizing and understanding health needs in marginalized areas. Sociodemographic and epidemiological factors serve as a foundation for developing strategies and optimizing resources in the social-health care of PWD. This study is a pioneer in deepening disability care in rural areas.